Narrating Illness as an Alternative Narrative through Salma Saleh's The Year of Cancer - Sami Abdul-Nabi, Prof .Dr. Ishraq (Basra studies journal, 2024)
In this book, writing about a frightening disease such as cancer took a special style that does not rely on repeated clichés or stereotypical ideas, but rather it is a lived experience in its details without being overwhelmed by human feelings and emotions during fear and major shocks. This book is an alternative narrative to the idea of ​​illness that came about by getting rid of the dominance of metaphors and the emotional weight that accompanies the patient and that is transmitted to him through general perceptions that make him bear a hidden guilt in the illness instead of giving him understanding and support.